2011
DOI: 10.1074/jbc.m111.218321
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion-dependent N-terminal Processing of Outer Membrane Mcl-1 Protein Removes an Essential Mule/Lasu1 Protein-binding Site

Abstract: Mcl-1, a pro-survival member of the Bcl-2 family located at the mitochondrial outer membrane, is subject to constitutive ubiquitylation by the Bcl-2 homology 3-only E3 ligase, Mule/ Lasu1, resulting in rapid steady-state degradation via the pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Single spanning signal-anchored proteins like OPA3 do not typically require a membrane potential for their import nor do they require any of the known import components for their insertion and to date, little is known about their import (reviewed in Dukanovic and Rapaport, (2011)). Thus it is not clear why CCCP should impact import of the OPA3 anchor, however it is interesting to note that currently there is discrepancy regarding membrane potential mediated processing of the outer mitochondrial membrane protein Mcl-1 (Warr et al, 2011; Yang-Yen, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Single spanning signal-anchored proteins like OPA3 do not typically require a membrane potential for their import nor do they require any of the known import components for their insertion and to date, little is known about their import (reviewed in Dukanovic and Rapaport, (2011)). Thus it is not clear why CCCP should impact import of the OPA3 anchor, however it is interesting to note that currently there is discrepancy regarding membrane potential mediated processing of the outer mitochondrial membrane protein Mcl-1 (Warr et al, 2011; Yang-Yen, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…For example, Bcl-x L reportedly regulates ATP synthesis by interacting with the F 1 F 0 ATP synthase (Alavian et al 2011). A fast-mobility isoform of Mcl-1 resulting from protease cleavage of the N terminus, like a subfraction of Bcl-x L , is localized to the mitochondrial matrix, suggesting other mitochondrial functions for Mcl-1 (Huang and Yang-Yen 2010), although this finding remains controversial (Warr et al 2011). Bax and Bak have also been implicated in the dynamics of mitochondrial fusion and fission (Martinou and Youle 2011), and binding of Bak by Mcl-1 might also alter mitochondrial function by altering these dynamics.…”
Section: Multitasking and Mcl-1 Biologymentioning
confidence: 93%
“…The matrix targeted isoform is produced following N terminal processing by a matrix processing protease during MCL-1 import into mitochondria [75, 77]. However, other studies indicated that the N terminus of MCL-1 can be cleaved to produce a shorter isoform that remains at the outer mitochondrial membrane [78]. The production of the shorter membrane-bound isoform depends on an intact mitochondrial membrane potential [78], but the protease in charge has not been characterized.…”
Section: Bcl-2 Proteins and Mitochondrial Electron Transport Chain Acmentioning
confidence: 99%
“…However, other studies indicated that the N terminus of MCL-1 can be cleaved to produce a shorter isoform that remains at the outer mitochondrial membrane [78]. The production of the shorter membrane-bound isoform depends on an intact mitochondrial membrane potential [78], but the protease in charge has not been characterized. While the precise molecular details of MCL-1 processing to these different isoforms remain to be worked out, evidence indicates that these isoforms do not share similar functions.…”
Section: Bcl-2 Proteins and Mitochondrial Electron Transport Chain Acmentioning
confidence: 99%